Clinical variability in two Macedonian families with Arterial tortuosity syndrome - M Kocova; R Kacarska; K Kuzevska-Maneva; S Prijic; M Lazareska; C Dordoni; M Ritelli; M Colombi (Macedonian Academy of Sciences and Arts / Walter de Gruyter GmbH, 2018)
Arterial tortuosity syndrome (ATS) is a rare autosomal recessive disorder caused by mutations in the solute carrier family 2 member 10 (SLC2A10) gene encoding a glucose/ascorbic acid transporter. The clinical features of ATS are mild-to-severe tortuosity of the large and medium arteries throughout the body, accompanied by dysmorphisms and joint laxity. Vascular changes in different parts of the body lead to stenosis and/or aneurysms requiring difficult surgical procedures. Here we present two new patients with ATS from two unrelated families. Patient 1 presented at 10 years of age with headache and typical physical appearance, delicate skeleton, large visible pulsation of the carotid arteries in the neck, and joint laxity. On computed tomography (CT) angiography she had severe tortuosity of the aortal branches and cerebral arteries, but no significant tortuosity of the pulmonary arteries. Two cousins of the girl carried the same homozygous c.254T>C, p.(Leu85Pro) mutation in SLC2A10, however, they additionally had a severe involvement of the pulmonary vessels. Patient 2 was a 9-year-old girl diagnosed with severe tortuosity and stenosis of the pulmonary arteries and progressive myocardiopathy. Her physical appearance was very similar to Patient 1, except that she also had growth retardation. After long-term follow-up by cardiologists, she underwent cardiac surgery abroad, with an unfavorable outcome. Homozygosity for the c.685C>T, p.(Arg229*) mutation in the SLC2A10 gene was detected. Consanguinity was disclosed within both families. Our findings confirm the intrafamilial phenotype variability of ATS. A novel finding is the severe tortuosity of cerebral arteries causing migraine that has not been described before in a child with ATS.